PENGARUH ARANG SEKAM TERHADAP PERTUMBUHAN BIBIT KAKAO(Theobroma cacao L.) PADA TANAH PASCA TAMBANG - Meivia Suprianti; Rosmalinda Rosmalinda; Tardi Kurniawan (Politeknik Negeri Ketapang, 2025)
Cocoa (Theobroma cacao L.) is one of the export commodities that can contribute to increasing Indonesia's foreign exchange. This study aims to determine the effect of rice husk charcoal on the growth of cocoa seedlings in post-mining soil and the best dosage for the growth of cocoa seedlings. This study used a completely randomized design (CRD) with 6 treatments and 4 replications. Each replication consisted of 3 plant samples, resulting in 72 plant samples. The treatments were: P0: Without Rice Husk Charcoal, P1: Rice Husk Charcoal 350 g/polybag, P2: Rice Husk Charcoal 450 g/polybag, P3: Rice Husk Charcoal 550 g/polybag, P4: Rice Husk Charcoal 650 g/polybag, and P5: Rice Husk Charcoal 750 g/polybag. The parameters observed were seedling height, stem diameter, number of leaves, root length, dry weight of the crown, dry weight of the root, and soil pH. The results of the DMRT test showed that the treatment of 650 g/polybag rice husk charcoal could affect seedling height, root length, dry weight of the shoot, dry weight of the root, and soil pH.